2008
DOI: 10.1529/biophysj.107.124487
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Study of Talin-Vinculin Binding

Abstract: Cells can sense mechanical force in regulating focal adhesion assembly. One vivid example is the force-induced recruitment of vinculin to reinforce initial contacts between a cell and the extracellular matrix. Crystal structures of the unbound proteins and bound complex between the vinculin head subdomain (Vh1) and the talin vinculin binding site 1 (VBS1) indicate that vinculin undergoes a conformational change upon binding to talin. However, the molecular basis for this event and the precise nature of the bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 39 publications
2
48
0
Order By: Relevance
“…There are several sites on the talin rod that bind the vinculin head [Ziegler et al, 2008]. The majority of these sites are cryptic (buried inside the rod), but can be opened by unfolding the talin molecule, as was proposed in structural studies [Fillingham et al, 2005; Gingras et al, 2006; Papagrigoriou et al, 2004], verified by steered molecular dynamic simulations [Hytonen and Vogel, 2008 ; Lee et al, 2007, 2008], and finally directly demonstrated in experiments involving the stretching of talin rods in vitro [del Rio et al, 2009]. Notably, binding of the vinculin head to talin promotes binding of the vinculin tail to the actin filament [Bois et al, 2006].…”
Section: Adhesion-dependent Mechanosensitivity: Phenomenology and Elementioning
confidence: 99%
“…There are several sites on the talin rod that bind the vinculin head [Ziegler et al, 2008]. The majority of these sites are cryptic (buried inside the rod), but can be opened by unfolding the talin molecule, as was proposed in structural studies [Fillingham et al, 2005; Gingras et al, 2006; Papagrigoriou et al, 2004], verified by steered molecular dynamic simulations [Hytonen and Vogel, 2008 ; Lee et al, 2007, 2008], and finally directly demonstrated in experiments involving the stretching of talin rods in vitro [del Rio et al, 2009]. Notably, binding of the vinculin head to talin promotes binding of the vinculin tail to the actin filament [Bois et al, 2006].…”
Section: Adhesion-dependent Mechanosensitivity: Phenomenology and Elementioning
confidence: 99%
“…3 Altered conformations of the tandem repeats may trigger downstream signaling cascades, for instance by modulating binding to filamin interacting protein and downstream pathways. 3 Furthermore, phosphorylation of filamin A at Ser 21,52 appears to promote force-induced unfolding and affinity for integrin. 18 A recent single-molecule experiment with optical tweezers on filamin A showed another potential mechanism for mechanosensing based on force-induced cis–trans proline isomerization of the force sensing domain pair 20–21 in filamin A.…”
Section: Atomistic Scale: Forces and Structurementioning
confidence: 99%
“…Specifically, it is important to characterize how the three-dimensional structural rigidity of DNA, RNA and proteins control their deformation under various loading conditions—stretching, twisting, bending and shear conditions—and how such deformation alters DNA condensation, gene replication and transcription, DNA–protein/RNA–protein interactions, protein function, protein–protein interaction, and protein–ligand interaction 5–7,14,48,51,53,71. These research topics encompass bond formation, reaction rates, and the thermodynamics and kinetics of biomolecular interactions.…”
Section: Molecular Biomechanics: An Emergent Fieldmentioning
confidence: 99%
“…To date, the molecular mechanisms of force sensing and mechanotransduction remain elusive. While numerous mechanisms have been proposed, a strong candidate for the molecular mechanism of mechanosensing and mechanotransduction is protein deformation, or protein conformational change under force 41,51,53,87,95,96. The unique three-dimensional structure (i.e., conformation) of a protein largely determines its function.…”
Section: Major Issues and New Opportunitiesmentioning
confidence: 99%